Growth theory - Dasgupta, Dipankar (New Delhi, 2005)
The problem of economic growth today constitutes one of the most important concerns facing policy planners from developing as well as developed countries. This has triggered renewed interest in growth economics among theorists. This volume highlights some recent advances in growth theory including: BL long run growth BL financing infrastructure BL taxation policies BL resource allocation for technogocial progress BL human capital formation The author uses a common framework to analyse different models and to highlight and compare distinguishing features of individual models. Solow's neo-classical model of growth is used as a basic reference point to build other ideas. Based on the experience of the author in the clasrooms, the book uses undergraduate mathematics for a lucid and simple exposition of growth economics. The volume will be of immense value as a textbook for senior undergraduate and postgraduate students, and research scholars, as well as a teaching and research tool.
Keywords: Economic development